Transnationalism and the transforming roles of professional accountancy bodies. Issue 6 (31st July 2014) - Paul Gillis, Professor Richard Petty; Professor Roy Suddaby, Professor; Samsonova-Taddei, Anna; Humphrey, Christopher
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The accounting regulation literature has recently devoted a significant degree of attention to delineating the roles of accounting firms as key professional actors in the transnational policy arena. Such a heightened level of scholarly engagement with firms seems to have shifted the focus away from the roles of the national professional institutes. The purpose of this paper is to demonstrate the importance of not losing sight of the national professional bodies as important players on the transnational governance scene. Design/methodology/approach – The accounting regulation literature has recently devoted a significant degree of attention to delineating the roles of accounting firms as key professional actors in the transnational policy arena. Such a heightened level of scholarly engagement with firms seems to have shifted the focus away from the roles of the national professional institutes. The aim with this paper is to demonstrate the importance of not losing sight of the national professional bodies as important players on the transnational governance scene. Findings – The paper provides empirical illustrations and discussion of the transforming agendas and strategies of influence pursued by various national professional bodies as they attempt to reinvent themselves to face up to the challenges of the changing regulatory landscape. Specifically, the paper analyses a range of activities where such bodies are seen to be competing with each other as well as partaking in a variety of collaborative initiatives in their quest to gain/maintain the status of a global/regional professional thought leader. Practical implications – The paper is designed to encourage renewed academic debate on the roles and strategies of national professional institutes and highlight opportunities and venues for future research. The paper is also suggestive of the need to refine conceptual perspectives on professionalization processes operational in transnational settings. Originality/value – The accounting literature is lacking in terms of contemporary study of national professional bodies as active institutions with global ambition and strategies of influence. This paper addresses such a shortcoming by analysing the strategic intent and actions of a range of such bodies (revealing, in the process, a quite fascinating complex of activity, competition and cooperation) and calling for a renewed focus on national professional bodies as a way of enhancing contemporary understanding of the workings of the "global accounting profession".